Public health responses during measles outbreaks in elimination settings: Strategies and challenges - Paul A. Gastañaduy; Emily Banerjee; Chas DeBolt; Pamela Bravo-Alcántara; Samia A. Samad; Desiree Pastor; Paul A. Rota; Manisha Patel; Natasha S. Crowcroft; David N. Durrheim (Taylor & Francis Group, 2018)
In late September 2016, the Americas became the first region in the world to have eliminated endemic transmission of measles virus. Several other countries have also verified measles elimination, and countries in all six World Health Organization regions have adopted measles elimination goals. The public health strategies used to respond to measles outbreaks in elimination settings are thus becoming relevant to more countries. This review highlights the strategies used to limit measles spread in elimination settings: (1) assembly of an outbreak control committee; (2) isolation of measles cases while infectious; (3) exclusion and quarantining of individuals without evidence of immunity; (4) vaccination of susceptible individuals; (5) use of immunoglobulin to prevent measles in exposed susceptible high-risk persons; (6) and maintaining laboratory proficiency for confirmation of measles. Deciding on the extent of containment efforts should be based on the expected benefit of reactive interventions, balanced against the logistical challenges in implementing them.